Mediterranean diet and magnetic resonance imaging-assessed cerebrovascular disease. - Scarmeas, Nikolaos; Luchsinger, José A; Stern, Yaakov; Gu, Yian; He, Jing; DeCarli, Charlie; Brown, Truman; Brickman, Adam M (Ann Neurol, 2011)
OBJECTIVE: Cerebrovascular disease is 1 of the possible mechanisms of the previously reported relationship between Mediterranean-type diet (MeDi) and Alzheimer's disease (AD). We sought to investigate the association between MeDi and MRI infarcts. METHODS: High-resolution structural MRI was collected on 707 elderly 65 years or older community residents of New York with available dietary assessments administered an average of 5.8 years (3.22 standard deviations [SDs]) before the MRI. Participants were divided into 3 groups of adherence to MeDi (low, middle, and high tertiles). We examined the association of increasing adherence to MeDi with presence of infarcts on MRI. Models were run without adjustment, adjusted for basic demographic and clinical factors, and adjusted for vascular risk factors. RESULTS: A total of 222 participants had at least 1 infarct. In the unadjusted model, compared to the low adherence group, those in the moderate MeDi adherence group had a 22% reduced odds of having an infarct (odds ratio [OR], 0.78; 95% confidence interval [CI], 0.55-1.14), while participants in the highest MeDi adherence group had a 36% reduced odds (OR, 0.64; 95% CI, 0.42-0.97; p for trend = 0.04). In adjusted models, the association between MeDi adherence and MRI infarcts remained essentially unchanged. The association of high MeDi adherence with infarcts was comparable to that of hypertension (40% reduced probability), did not vary by infarct size or after excluding patients with dementia (n = 46) or clinical strokes (n = 86). There was no association between MeDi and white matter hyperintensities. INTERPRETATION: Higher adherence to the MeDi is associated with reduced cerebrovascular disease burden.
Keywords: Aged; Aged, 80 and over; Aging; Analysis of Variance; Brain; Brain Mapping; Cerebrovascular Disorders; Diet, Mediterranean; Female; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Motor Activity; Neurologic Examination; Neuropsychological Tests; New York; Risk Factors